2016
DOI: 10.21082/jhort.v23n3.2013.p244-254
|View full text |Cite
|
Sign up to set email alerts
|

Komposisi Formula Biobakterisida Berbahan Aktif Rizobakteri untuk Pengendalian Penyakit Busuk Lunak Pada Anggrek Phalaenopsis

Abstract: <p>Penyakit busuk lunak (PBL) yang disebabkan oleh Pectobacterium carotovorum subsp. carotovorum atau Pseudomonas viridiflava merupakan kendala utama dalam budidaya anggrek. Serangan patogen tersebut sangat merugikan petani, mengingat biaya investasi produksi anggrek tergolong tinggi. Oleh karena itu patogen tersebut harus dikendalikan menggunakan metode pengendalian yang ramah lingkungan, yaitu dengan mengaplikasikan biobakterisida berbahan aktif rizobakteri, seperti Bacillus subtilis dan Pseudomonas fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Bacterial consortium gave a better result to suppress the P. coffeae population and enhance e coffee plant growth. The bacterial consortium formulation as biofertilizer and biopesticide with molasse media has also been reported to be effective in the previous studies (Hanudin et al 2016). Kumari et al (2019) reported that molasse could be used as cheap formulation media, easily obtained, environmentally safe, capable of supporting bacterial life during the preservation period.…”
Section: Discussionmentioning
confidence: 95%
“…Bacterial consortium gave a better result to suppress the P. coffeae population and enhance e coffee plant growth. The bacterial consortium formulation as biofertilizer and biopesticide with molasse media has also been reported to be effective in the previous studies (Hanudin et al 2016). Kumari et al (2019) reported that molasse could be used as cheap formulation media, easily obtained, environmentally safe, capable of supporting bacterial life during the preservation period.…”
Section: Discussionmentioning
confidence: 95%